Ethnic heterogeneity and public goods provision in Zambia: Further evidence of a subnational 'diversity dividend' - Rachel M. Gisselquist; Stefan Leiderer; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
The hypothesis that ethnic diversity has a negative impact on public goods provision is widely accepted. Notably, most work on this issue fails to distinguish adequately between national versus subnational governance. We find that subnational empirical evidence in particular is inconclusive, and speak to this gap with new analysis at the Zambian district level. Results lend strong support to an emerging body of work challenging the 'diversity debit' hypothesis: we find no clear evidence of a negative impact but instead a robust positive association with key welfare outcomes. Contra the conventional wisdom, future work should explore mechanisms underlying the 'diversity dividend' now suggested in multiple subnational analyses.
Keywords: D71; H41; H72; H75; I18; I28; 330; ethnic diversity; government performance; education; health; Zambia